1994
DOI: 10.1542/peds.93.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-Reactive Protein, Erythrocyte Sedimentation Rate, and White Blood Cell Count in Acute Hematogenous Osteomyelitis of Children

Abstract: Objective. The aim of this prospective study was to compare the clinical value of the erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and white blood cell (WBC) count in diagnosis and follow-up of acute hematogenous osteomyelitis in children. Design. Forty-four children aged 2 weeks to 14 years with bacteriologically confirmed acute hematogenous osteomyelitis were examined. Staphylococcus aureus was responsible in 39 cases (89%), Haemophilus influenzae type b in 3 cases (7%), pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…The levels of acute-phase reactants are usually high. 17,18 Hamidi et al 19 reported a significant difference in the levels of acute-phase reactants between patients with pyogenic spondylodiscitis and those with brucellar or tuberculous spondylodiscitis. In our study, the levels of acute-phase reactants were increased in all three groups, but the highest levels were observed in patients with tuberculous spondylodiscitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of acute-phase reactants are usually high. 17,18 Hamidi et al 19 reported a significant difference in the levels of acute-phase reactants between patients with pyogenic spondylodiscitis and those with brucellar or tuberculous spondylodiscitis. In our study, the levels of acute-phase reactants were increased in all three groups, but the highest levels were observed in patients with tuberculous spondylodiscitis.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of acute-phase reactants are usually high. 17,18 Hamidi et al. 19 reported a significant difference in the levels of acute-phase reactants between patients with pyogenic spondylodiscitis and those with brucellar or tuberculous spondylodiscitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient presented with symptoms classic for osteomyelitis. Laboratory findings seen in osteomyelitis include leukocytosis and elevated inflammatory markers [ 19 ]. He did have leukocytosis but not anemia and thrombocytopenia, thus excluding leukemia and low immunity [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Widely accepted markers are ESR/CRP/WBC count, but they lack sensitivity and specificity. 6,7 Recently, many studies have shown that serum procalcitonin (PCT) levels rise rapidly in response to bacterial endotoxins. 8e10 It can be used to differentiate septic from non-septic conditions.…”
Section: Introductionmentioning
confidence: 99%